Incidence of flexion distraction injuries of thoraco lumbar spine - S., Satheesh Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Thoraco-lumbar spine fractures form majority of spine fractures and is an important cause of morbidity. However, comprehensive data regarding epidemiological pattern of trauma patients with spinal fractures are scarce. Many epidemiological reports about spinal fractures focus on osteoporosis as an etiologic factor. But in Indian population more important etiological factors are road traffic accidents and falls from height. Studies concerning only operatively treated patients with spinal fractures show selective and biased data that might be useful for capacity planning in hospitals or evaluating results of operative treatment, but not for epidemiological purposes. Methods: Among 86 consecutive patients with thoracic or lumbar fractures attending the out-patient department or Emergency department of Sree Gokulam Medical College, Trivandrum were enrolled in the study. All patients with fractures of the thoracic or lumbar spine were enrolled in this study. Results: Flexion distraction injuries are the second commonest unstable thoracolumbar spine injuries. Conclusions: This study is a prospective cohort study of the epidemiological aspects and pattern of injury and treatment in thoraco-lumbar spine fractures at a tertiary care referral center. A total of 86 patients were enrolled in the study. The most common fracture pattern seen in this study was compression fractures (24.4%) which are stable. This was followed by stable burst fractures (23.2%, unstable burst fractures (18.6%), translational injuries (fracture-dislocations) (16.3%), flexion-distraction injuries (13.9%) and chance fractures (3.5%).